Tren Penelitian dan Kemajuan Teknologi pada Pelapisan HVOF untuk Komponen Mesin Pesawat Terbang (2020–2025): Tinjauan Sistematis dan Bibliometrik - Novia Ramadhani (Universitas Proklamasi 45, 2026)
High-Velocity Oxygen-Fuel (HVOF) coating technology has become a key approach in surface engineering for aircraft-engine components operating under extreme thermal and mechanical conditions. This review maps global research developments, identifies advances in deposition technology, and reveals remaining gaps through a systematic and bibliometric review of 20 Scopus-indexed publications from 2020 to 2025. Using PRISMA-based screening and VOSviewer, the study analyzed publication trends, thematic clusters, and collaboration patterns. The results show a sharp publication increase in 2025 and indicate that 65% of the reviewed studies focused on High-Entropy Alloy and Medium-Entropy Alloy coatings. Major findings include a 40% increase in nano-hardness after post-deposition annealing, successful phase prediction using Scheil-CALPHAD simulation, and the growing role of HVAF as a complementary method with lower oxidation and higher coating density for selected applications. HVOF nevertheless remains the dominant process because of its mature industrial use, dense coatings, and strong adhesion. Future research should integrate computational modeling, real-service degradation studies, and artificial-intelligence-based optimization for aerospace coating design.